Factors Determinant Bushmeat Consumption Pattern in 4 Provinces in Lao PDR - Khongsavanh, Souksavanh; Vang , Vadao (International Journal of Multidisciplinary in Management and Tourism, 2020)
The purpose of this study is to examine the factors influences bushmeat consumption in Lao PDR. The authors use cross-sectional data that are collected from 654 household from 4 areas: Vientiane capital, Vientiane province, Luangprabang province, and Xiengkhuangprovince in 2018, and the Logistic Regression Model is used for the analysis. This study finds that gender, household expenditure, belief and law awareness have the positive impact on bushmeat consumption. The authors conclude that gender, household expenditure, travel to other province, believe that bushmeat good for health and conservation awareness have affected on bushmeat consumption.Wildlife policy-makers should be aware that conservation law has positively impact on bushmeat consumption, so the government should put more effort to make the wildlife conservation law sufficiency. This finding might have significant impacts on reducing wild meat consumption in Lao PDR and provide information for further research in this areas.